FEATURES OF TEACHING MATHEMATICAL ANALYSIS FOR STUDENTS OF TRAINING DIRECTION - INFORMATICS (Journal of Information Technologies in Education (ITE), 2011)
This paper explains the need and provides the main stages of the development of new curricula "Mathematical analysis" for students training areas - computer science, which includes the study of the possible applications of mathematical analysis in information processing algorithmic methods using computer technology.
Keywords: algorithmic methods; computer science; information; mathematical analysis; training program